Investigation of ferro-resistive switching mechanisms in TiN/Hf0.5Zr0.5O2/WOx/W ferroelectric tunnel junctions with the interface layer effect - Lee, Suk Hyun; Park, Han Sol; Shin, Seong Jae; Lee, In Soo; Ryoo, Seung Kyu; Byun, Seungyong; Kim, Kyung Do; Moon, Taehwan; Hwang, Cheol Seong (Applied Physics Reviews, 2024)
This study presents an in-depth analysis of ferro-resistive switching (FRS) behaviors in a TiN/Hf0.5Zr0.5O2(HZO)/WOx/W ferroelectric tunnel junction (FTJ) device, with a particular focus on the role of the tungsten oxide (WOx) interface layer (IL). Structural examinations confirm the presence of the WOx IL, which significantly influences the FRS properties of the device. Electrical measurements indicate the devices exhibit stable and reproducible FRS characteristics with an ON/OFF ratio of 9.7, predominantly attributed to the tunneling electro-resistance (TER) effect driven by the ferroelectric polarization. Comprehensive numerical simulations, incorporating the nucleation-limited switching model and Simmons tunneling mechanism, provide detailed insights into how the WOx IL and the trapped charges at the HZO/WOx interface affect polarization switching mechanisms and the electronic potential barrier profile. These findings underscore the importance of interface effects in HfO2-based FTJs and advance the understanding of the TER mechanism in multilayer ferroelectric systems.
Keywords: Ferroelectric tunnel junctions; In-depth analysis; Interface layer; Junction devices; Resistive switching; Resistive switching behaviors; Resistive switching mechanisms; Structural examination; Switching properties; Tungsten oxide